Promoting Storytelling in Enhancing Health Vocational Students’ Speaking Achievement - Istanto, Wisnu; Candra, Diah Arumita; Heryani, Heni (CV. Creative Tugu Pena, 2021)
Soft skills development requires the use of education media and forums. While storytelling may be used in competitions, media classes do not use it as a teaching media. Storytelling in the classroom hasn't been used to its fullest potential. English language proficiency can be improved through the use of digital storytelling, specifically on YouTube, by students. The study is intended to achieve similarities and discrepancies in the importance of the English-language achievement with general English and the implementation of digital storytelling. This study may be graded as an experimental investigation and classroom action research. This study employed cross-sectional research with independent speaking pre-test and post-test for experimental and control group design. Talking with storytelling therapy triggering different strategies is advised in experimental classes. It uses intervention research to change people's